A STUDY OF PHYSICAL AND CHEMICAL PROPERTIES IN FIBERS OF PATTAWIA, NANGLAE, AND PHULAE PINEAPPLE GROWN IN CHIANGRAI PROVINCE - Intaro, Taworn; Jaita, Subin; Netsuwan, Paphawadee (Srinakharinwirot University Journal of Sciences and Technology, 2024)
This research aims to study the physical and chemical properties of fibers from pineapple leaves of Pattawia, NangLae, and PhuLae which growing in Chiang Rai province. The fibers were produced using a mechanical method. Then, the obtained fibers were tested and analyzed for physical properties such as surface, fineness, tensile strength, tenacity, and elongation, as well as chemical properties such as their elements and major chemical composition. The research found that Pattawia and NangLae pineapple fibers had a mean diameter of 77.64±24.89 and 80.82±34.79 micrometers, respectively, while PhuLae fibers had approximately of 67.32±22.96 micrometers. Regarding fineness of Pattawia, NangLae, and PhuLae fibers, they were 52, 54, and 48 deniers, respectively. Their tensile strengths were 317.38±102.91, 308.75±62.02, and 244.65±139.68 megapascals, respectively. The tenacities were 4.42±0.52, 2.99±0.39, and 4.58±1.02 grams/denier, respectively, and the elongations were 4.79±0.85, 4.76±0.45, and 7.38±1.77%, respectively. In terms of chemical properties, all three types of fibers primarily consisted of carbon and oxygen, which related to the result of the major chemical composition that is Pattawia and NangLae fibers had cellulose 47.62% and 42.86%, respectively, while PhuLae fibers had 35.10%. When analyzing the hemi-cellulose content, PhuLae fibers had the highest quantity at 36.73%, while Pattawia and NangLae had closely at 23.81% and 22.86%, respectively. Regarding lignin content, all three types had similar quantities, as follows, Pattawia is at 20.00%, NangLae is at 17.14%, and PhuLae is at 19.35%. In concluding, all three types of fibers possess physical and chemical properties suitable for textile use, particularly PhuLae fibers, which have fine fineness, tenacity and elongation. They fit to make a textile product and cause to feel comfortable and lightweight.